An in vitro study of probiotic activity exhibited by Lactobacillus acidophilus and Lactobacillus rhamnosus on oral isolates of Streptococcus mutans and Candida albicans - Naushad, Ameena M.; Sunil, Jenny M.; Kumar K. S., Harish; Sathar, Sajimi; Mathews, Roopa; Gopal, Anila (International Journal of Research in Medical Sciences, 2023)
Background: Oral infections caused by microorganisms have led to increased risk of oral health problems like dental caries (DC). Streptococcus mutans and Candida albicans are the organisms responsible for DC. The goal of the presented study was to investigate the potential of probiotics to prevent and treat DC. An in vitro assay was developed to investigate several probiotic strains for their ability to inhibit the aforementioned oral pathogens. Methods: 40 oral isolates of Streptococcus mutans and 51 oral isolates of Candida albicans were tested for probiotic activity against Lactobacillus acidophilus and Lactobacillus rhamnosus using agar overlay interference technique as prescribed by Fleming et al. Results: The zone of inhibition shown by L. acidophilus was higher than L. rhamnosus against Streptococcus mutans and Candida albicans. Conclusions: In conclusion the two probiotic strains L. acidophilus and L. rhamnosus exhibited inhibitory activity on S. mutans and C. albicans respectively in vitro.